Optimization of rabbit urine liquid organic fertilizer and reduced NPK fertilizer doses for improving growth and physiology of shallot (Allium ascalonicum L.) - Tini, Etik Wukir; Kurniawan, Rifqi Raditya (Universitas Padjadjaran, 2025)
Rabbit urine liquid organic fertilizer (LOF) can be used as an alternative fertilizer to reduce the use of inorganic fertilizers, especially for shallots, as a national food commodity. This study aims to determine the best concentration of rabbit urine LOF, the best dose of NPK fertilizer dose reduction, and a combination of rabbit urine LOF and NPK fertilizer dose reduction on the physiological characters of shallot plants. The observed variables consisted of net assimilation rate, crop growth rate, stomatal density, stomatal aperture, and chlorophyll content. The experimental results showed that a concentration of 200 mL L-1 of rabbit urine LOF had the best effect on several physiological characteristics studied. In addition, a 50% reduction in the NPK dose had the best effect on physiological characteristics compared to other treatments. Rabbit urine LOF 200 mL L-1 and a 50% reduction in NPK doses had a significant interaction effect on the physiological characters of shallot plants.